PENGARUH GAME BASED LEARNING (GBL) BERBASIS MEDIA QUIZIZZ TERHADAP PEMAHAMAN PADA MATERI DATA DAN DIAGRAM DI SMP ISLAM AL-MALIKI WOHA - Jumratul Aqabah; Nanang Diana; Arif Hidayad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of implementing the Game-Based Learning (GBL) model assisted by Quizizz media in enhancing students’ understanding of mathematical concepts on the topic of Data and Diagrams at SMP Islam Al-Maliki Woha. The background of this research lies in the low level of students’ conceptual understanding of mathematics and the lack of interactive learning media used in classrooms. The method employed in this study is Quasi-Experimental with a Non-equivalent Control Group Design. The research subjects consisted of two classes: Class VIIA as the experimental group and Class VIIB as the control group, each comprising 20 students. The research instrument was a conceptual understanding test that had been validated both in terms of content and construct. The data analysis results indicated a significant improvement in students' conceptual understanding in the experimental group after using Quizizz, as shown by the independent t-test results with a significance value of 0.000 (< 0.05) and a post-test mean score difference of 29.1 points. The obtained data also met the assumptions of normality and homogeneity. These findings suggest that the use of Quizizz provides a more enjoyable, competitive, and participatory learning experience, and is capable of increasing student motivation and understanding. Therefore, integrating Quizizz-based GBL is considered an effective and innovative learning strategy for teaching mathematics in the digital era.